Coherence for health innovation for new medicines for infectious diseases. (The developement dimension., 2009)
In developing countries, 6 out of 10 people die from infectious diseases. Nearly 1 billion humans suffer from a neglected infectious disease, according to the World Health Organization. Yet less than 1% of the new drugs placed on the market from 1975 to the turn of the century were developed for these diseases. This book looks at ways of improving the availability of medicines for infectious diseases through strengthened coherence in health, trade, science and technology, development cooperation and finance.--Publisher's description.